Implementasi Algoritma C4.5 Untuk Klasifikasi Penentuan Penerima Bantuan Langsung Tunai Di Desa Tanjung Rejo - Sri Juwita; Muhathir Muhathir; Rizki Muliono (Jurnal Ilmiah Teknik Informatika & Elektro (JITEK), 2022)
Direct Cash Assistance (BLT) provides money to the poor. This cash assis-tance program was made to help the underprivileged deal with the corona-virus (Covid 19) pandemic. The implementation of the C4.5 algorithm in determining the recipients of Direct Cash Assistance (BLT) was conducted by making classifications or rules according to the data of the old benefi-ciaries, then classifying based on the variables of the husband's and wife's work, home status, and the number of dependents. The results of these classifications or rules were used as a basis if there were future Direct Cash Assistance (BLT) recipients. Through the application of the C4.5 algorithm in determining the exact target of Direct Cash Assistance (BLT), beneficiar-ies could receive assistance quickly and then would be shown in a report that could be downloaded.